2019
DOI: 10.1371/journal.pone.0212737
|View full text |Cite
|
Sign up to set email alerts
|

Lowering the upper limit of serum alanine aminotransferase levels may reveal significant liver disease in the elderly

Abstract: This study sought to determine the prevalence of significant liver disease in those subjects with serum alanine aminotransferase levels in the range between the current and the newly suggested upper limit of normal (termed the delta range). The files of the previous study subjects (who underwent at least one alanine aminotransferase measurement in 2002 and followed to 2012) were reviewed for a diagnosis of chronic liver disease; aspartate aminotransferase/platelet ratio index, FIB-4 and alanine aminotransferas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Thus, decreasing liver transaminase in aged livers may lead to these conditions during ageing in response to diseases. Moreover, older individuals who meet the currently accepted normal range of ALT may harbour clinically significant liver disease [ 35 ]. Low ALT activity in older people is associated with greater mortality [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, decreasing liver transaminase in aged livers may lead to these conditions during ageing in response to diseases. Moreover, older individuals who meet the currently accepted normal range of ALT may harbour clinically significant liver disease [ 35 ]. Low ALT activity in older people is associated with greater mortality [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the highest tissue concentration of alanine transaminase (ALT) activity is in the cytosol of hepatocytes, it is found throughout the human body, in the kidney, myocardium, skeletal muscle, brain, pancreas, spleen, and lung [3]. It has been reported that lowering the normal value of alanine transaminase (ALT), whose blood value is 15-42 IU/L for men and 10-26 IU/L for women, is bene cial in diagnosing liver diseases in elderly patients, and this value is associated with mortality [4,5].…”
Section: Introductionmentioning
confidence: 99%